Comparative Politics : the State of the Subdiscipline - Laitin, David (Standford University, 2000)
In earlier decades, there was a consensus about a specific comparative method. It was differentiated from a statistical and from a case-study methodology, and it emphasized through the use of strategic controls the isolation of key variables that could explain variations in outcomes. However, Laitin argues that this consensus is no longer representative of the field.